ZOOM LEARNING MEDIA RELATIONSHIP AND INTEREST IN LEARNING WITH LEARNING OUTCOMES CIVICS - Pardan Prasetyo; Zainal Abidin (Akademika, 2023)
This study aims: 1) To find out the relationship between Zoom learning media and Civics learning outcomes. 2) To determine the relationship between students' interest in learning with Civics learning outcomes. 3) To determine the relationship between Zoom learning media and students' interest in learning and Civics learning outcomes. This study uses survey methods and correlational techniques. The target population reached in this study were all students of class IX in CIVICS at SMPN 1 Tajurhalang, a total of 371 students. Data retrieval using the instrument of learning outcomes for Civics subjects and questionnaires for learning media zoom and interest in learning. The data analysis technique used descriptive and inferential analysis.Based on the results of the analysis using descriptive statistics at SMPN 1 Tajurhalang, the average value was 83.8 for civics learning outcomes, 78.3 for Zoom learning media, and 80.88 for interest in learning. The analysis of simple regression analysis and correlation with the ANOVA test obtained that the media correlation coefficient (rxy) = 0.137 indicates that the relationship between X1 and Y has a strong relationship level. Then the correlation coefficient (rxy) = 0.355 indicates that the relationship between X2 and Y has a strong level of relationship. The study results show that 1) There is a positive relationship between Zoom learning media and civics learning outcomes. 2) There is a positive relationship between interest in learning and learning outcomes of Civics. 3) There is a positive relationship between Zoom learning media and interest in learning and Civics learning outcomes